Measurement of length and weight on non-articulated adult humerus in Nepalese corpses - Niraj, P; Dangol, PMS; Ranjit, N (Journal of Kathmandu Medical College, 2014)
Background: Anthropometry is the science that deals with the measurement of size, weight and proportion of humanbody. Measurements of long bones play an important role in the estimation of stature of individuals in palaeoanthropologyand forensic investigations. Objectives: The objectives of this study were to determine length and weight of humerus in Nepalese population and tocompare these with the data from other population for use in forensic and archaeological studies. Methods: This is a descriptive study. A total of 200 (100 right, 100 left) humerus bones were included. The Maximumhumerus length (mm) was measured by osteometric board and weight (g) of the humerus was measured by electronicweighing machine. Results: The mean and standard deviation for humerus length and weight of humerus were found to be 308.580±19.169mm and 122.261 g for right humerus and 307.270±16.1301 mm and 118.473 g for left humerus respectively. Conclusion: In conclusion, our measurements on the humerus have demonstrated that the length and weight ofhumerus in Nepalese population is similar to that of other country population values. DOI: http://dx.doi.org/10.3126/jkmc.v2i1.10550 Journal of Kathmandu Medical College, Vol. 2, No. 1, Issue 3, Jan.-Mar., 2013, page : 25-27